The Influence of Revenue Growth Rate and Initial Public Offering on Stock Price Estimation - Sri Lestari Yuli Prastyatini; Dini Resita (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the impact of Revenue Growth Rate and Initial Public Offering (IPO) on the projected stock prices of e-commerce companies listed on the Indonesia Stock Exchange between 2020 and 2023. Utilizing a quantitative approach, the research employs multiple linear regression analysis on secondary data from 30 e-commerce firms. The findings indicate that both Revenue Growth Rate and IPO have significant and positive effects on estimated stock prices, with a strong correlation between revenue growth and stock prices. While a sample size of 30 firms may seem adequate, the study could benefit from exploring the representativeness of this sample concerning the broader e-commerce industry, as a small sample size may introduce bias. Comparative analysis with similar markets, such as Southeast Asia, could provide additional context. Furthermore, it is essential to conduct further examination of the long-term effects of IPOs on stock prices, including price behavior in the 6 months to one year following the IPO, to yield deeper insights. These findings are expected to offer guidance for investors and stakeholders in making informed investment decisions within the e-commerce sector.